Camellia sinensis, a natural product to support the treatment of medical and stomatological conditions - Ricardo Reyes-Mansilla; Adelmo Cuentas-Robles; Donald Ramos-Perfecto (Universidad de Concepción., 2023)
Introduction: The tea plant, Camellia sinensis, is one of the most popular non-alcoholic beverages in the world. The main components of Camellia sinensis include amino acids, fatty acids, phenolic compounds, flavins and purine alkaloids (xanthines). For this reason, in the field of medicine, Camellia sinensis has been used as an anticancer, anxiolytic, antidiabetic, antiobesity, anti-inflammatory, analgesic, antipyretic, chemopreventive, cytotoxic and apoptogenic, genoprotective, hepatoprotective, nephroprotective, hemato-protective, and in wound healing, among other uses. Objective: To carry out a systematic review of the use of C. sinensis as supportive therapy in the treatment of oral disorders. Materials and Methods: This systematic review was carried out following the PRISMA guidelines. The search was carried out in the PubMed, ScienceDirect and Google Academic databases. Articles from studies of Camellia sinensis were reviewed and those from a secondary source, such as literature review articles, were excluded Results: A total of 12 full-text articles were selected for review, in which the properties of Camellia sinensis are detailed. Conclusions: According to the bibliography reviewed, C. sinensis exhibits anticariogenic properties, applications in the treatment of dental erosion, applications in the treatment of gingivitis and bacterial plaque, and applications in the prevention of oral cancer; however, more controlled clinical trials are needed to confirm its effectiveness and safety of use.